Hubungan Tingkat Pengetahuan Dengan Kejadian Hipertensi Pada Lansia Di Puskesmas Lerep - Jessica Ludowika Itlay; Silvia Nurvita (Jurnal Bisnis Kreatif dan Inovatif, 2024)
Background: Aging in human life is a natural thing, and must be experienced by all older people. Elderly is a phase characterized by the onset of weakness in the body and susceptibility to disease. Hypertension occurs over the age of 60 (55%.) Changeable factors such as knowledge. The aim of this study was to determine the relationship between the level of knowledge and hypertension in the elderly at the Lerep Community Health Center. Method: This research was conducted in February 2024 using a cross-sectional with 30 respondents. The level of knowledge as the independent variable, and hypertension in the elderly as the dependent variable. The instrument uses a questionnaire. Data analysis using the Kendal Tau test. Results: %. The results of the Kendal Tau statistical test obtained a p-value of 0.001<0.05, which means that there is a relationship between the level of knowledge and the incidence of hypertension in the elderly at the Lerep Community Health Center. Conclusion: the majority of respondents were aged 60-69 years (73.4%), 60% male, p-value 0.001, which means that there is a relationship between the level of knowledge and the incidence of hypertension. Suggestions for elderly people with hypertension can increase knowledge about managing hypertension.